Efektivitas Edukasi Miopia terhadap Peningkatan Pengetahuan, Sikap, dan Perilaku Santri Pondok Pesantren Ta’mirul Islam Surakarta - Husni Al Arifin Ali As-syafi’i; Ahmad Ikliluddin; Yunani Setyandriana (Lembaga Pengembangan Kinerja Dosen, 2025)
Myopia is an eye refractive disorder in which the light entering the eye is focused in front of the retina, causing long-distance vision to become blurry. This condition is often experienced by teenagers, including students in Islamic boarding schools, due to the habit of reading in close proximity, excessive use of gadgets, and lack of exposure to natural light. The high prevalence of myopia in young age groups needs serious attention so that it does not develop into permanent vision disorders. One of the prevention efforts that can be done is to provide education about myopia, including the definition, causes, prevention, and importance of maintaining eye health and a healthy lifestyle. This study aims to determine the effectiveness of myopia education on improving knowledge, attitudes, and behaviors of students of the Ta'mirul Islam Islamic Islamic Boarding School in Surakarta. Based on the results of the Wilcoxon Signed Rank Test and Paired Sample t-Test, there was a significant improvement in the aspects of knowledge and attitude, although behavioral changes have not shown meaningful results. These findings confirm the importance of continuous education to form healthy behaviors related to the prevention of myopia as a whole.